DIGITIZING TRAVEL: RETHINKING TOURISM IN THE AGE OF TECHNOLOGICAL ADVANCEMEN - Madina Abduqahhorova Abdumalik kizi; Mohinur Abdullayeva Umidulla kizi (TADQIQOTLAR, 2025)
Introduction In today’s world, where society is increasingly immersed in digital realities, tourism is undergoing a revolutionary transformation. As Donald Moriarty, an expert in travel innovations, aptly puts it, “We need a new understanding of tourism that isn’t limited to hotel walls or guided tour routes, but embraces the boundless world of digital possibilities.” Digital tourism, the focal point of this article, opens new horizons not only for travelers but also for entrepreneurs and stakeholders in the travel industry.